Size of the amino acid side chain at position 158 of cytochrome b is critical for an active cytochrome bc1 complex and for photosynthetic growth of Rhodobacter capsulatus. - Atta-Asafo-Adjei, E (1991)
The nonphotosynthetic mutant R126 of Rhodobacter capsulatus has a cytochrome (cyt) bc1 complex (EC 1.10.2.2) with a defective quinol oxidation Qz(o,p) site but a functional quinone reduction Qc(i,n) site. Genetic analyses of this mutant have indicated that a single-base-pair change has replaced Gly-158 of cyt b with Asp. In this work, Gly-158 was changed by oligonucleotide-mediated mutagenesis to several other amino acids to define its role on quinol oxidation catalyzed by the cyt bc1 complex. The effects of the mutations were analyzed by measuring the photosynthetic growth rate of mutants and the activity of their cyt bc1 complexes. The mutants overproduced the cyt bc1 complex, assembled its subunits, and incorporated its prosthetic groups as shown by immunoblotting and optical difference spectroscopy. Of 14 amino acid residues tested at position 158 of cyt b all but alanine and serine resulted in a marked decrease of cyt bc1 activity and failed to support photosynthetic growth of R. capsulatus. The photosynthesis-competent mutants, Gly-158----Ala and Gly-158----Ser, had lower cyt bc1 complex activities that were resistant to myxothiazol, but not to stigmatellin, quinol oxidation inhibitors. These findings indicated that the specific role of Gly-158 of cyt b on quinol oxidation and myxothiazol binding may be related to the small size of its side chain and are discussed in terms of the structure and function of the quinol oxidation site of the cyt bc1 complex.